Degradable Pseudo Conjugated Polymer Nanoparticles with NIR‐II Photothermal Effect and Cationic Quaternary Phosphonium Structural Bacteriostasis for Anti‐Infection Therapy. Issue 16 (27th March 2022) - Zhou, Huiling; Tang, Dongsheng; Kang, Xiaoxu; Yuan, Haitao; Yu, Yingjie; Xiong, Xiaolu; Wu, Nier; Chen, Fangzhou; Wang, Xing; Xiao, Haihua; Zhou, Dongsheng
Abstract: Photothermal therapy based on conjugated polymers represents a promising antibacterial strategy but still possesses notable limitations. Herein, degradable pseudo conjugated polymers (PCPs) containing photothermal molecular backbones and reactive oxygen species (ROS)‐sensitive thioketal bonds are designed. Triphenylphosphine (PPh3 ) is introduced into PCPs to generate phosphonium‐based PCPs (pPCPs), which further assembled with hyaluronic acid into pPCP nanoparticles (pPCP‐NPs). pPCP‐NPs with quaternary phosphonium cations selectively anchor on and destroy bacterial cell membranes through electrostatic action. Under 1064 nm laser irradiation, pPCP‐NPs (pPCP‐NPs/+L) produce near‐infrared‐II (NIR‐II) photothermal antibacterial effect, thereby killing bacteria in a sustained manner. pPCP‐NPs are readily degraded upon ROS abundant at infection sites, therefore exhibiting enough biosafety. pPCP‐NPs/+L display an almost 100% bacterial inhibition rate in vitro and resultin a nearly complete recovery of bacteria‐induced mouse wounds. A further metabolomics analysis denotes that pPCP‐NPs/+L work in a concerted way to induce bacterial DNA damage, inhibit bacterial carbon/nitrogen utilization and amino acid/nucleotide synthesis. Taken together, degradable pPCP‐NPs with both NIR‐II photothermal effect and cationic phosphonium structural bacteriostasis provide a new avenue for antibiotics‐alternative anti‐infection therapy. Abstract : pPCP nanoparticles (pPCP‐NPs) were developed to combine near‐infrared‐II (NIR‐II) photothermal effect with cationic phosphonium structural bacteriostasis. Under 1064 nm laser irradiation, pPCP‐NPs (pPCP‐NPs/+L) produce NIR‐II photothermal antibacterial effect, thereby killing bacteria in a sustained manner. Furthermore, the phosphonium structural bacteriostasis could destruct bacterial membrane. This combinational strategy provides a new avenue for antibiotics‐alternative anti‐infection therapy.